Pituitary adenylyl cyclase-activating polypeptide modulates the stress response: the involvement of different brain areas and microglia - Singh, Anika; Shim, Paul; Naeem, Sadaf; Rahman, Shafiqur; Lutfy, Kabirullah (Frontiers in Psychiatry, 2025)
Stress is necessary for survival. However, chronic unnecessary stress exposure leads to cardiovascular, gastrointestinal and neuropsychiatric disorders. Thus, understanding the mechanisms involved in the initiation and maintenance of the stress response is essential since it may reveal the underpinning pathophysiology of these disorders and may aid in the development of medication to treat stress-mediated diseases. Pituitary adenylyl cyclase activating polypeptide (PACAP) and its receptors (PAC1, VPAC1 and VPAC2) are expressed in the hypothalamus and other brain areas as well as in the adrenal gland. Previous research has shown that this peptide/receptor system serves as a modulator of the stress response. In addition to modulating the stress response, this system may also be connected to its emerging role as neuroprotective against hypoxia, ischemia, and neurodegeneration. This article aims to review the literature regarding the role of PACAP and its receptors in the stress response, the involvement of different brain regions and microglia in PACAP-mediated modulation of the stress response, and the long-term adaptation to stress recognizable clinically as survival with resilience while manifested in anxiety, depression and other neurobehavioral disorders.